How consistent are class size effects? - Spyros Konstantopoulos (Institute for the Study of Labor (IZA), 2009)
Evidence from Project STAR has suggested that on average small classes increase student achievement. However, thus far researchers have focused on computing mean differences in student achievement between smaller and larger classes. In this study I focus on the distribution of the small class effects at the school level and compute the inconsistency of the treatment effects across schools. I use data from Project STAR and estimated small class effects for each school on mathematics and reading scores from kindergarten through third grade. The results revealed that school-specific small class effects are both positive and negative and that although students benefit considerably from being in small classes in some schools, in other schools being in small classes is a disadvantage. Small class effects were inconsistent and varied significantly across schools. Full time teacher aide effects were also inconsistent across schools and in some schools students benefit considerably from being in regular classes with a full time aide, while in other schools being in these classes is a disadvantage.
Keywords: I20; 330; Small classes; treatment variability; meta-analysis; Klassengröße; Bildungsniveau; Wirkungsanalyse; Test; USA